THE SYNTHESIS OF CARBONDIOXIDE GAS USING SMALL SCALE EQUIPMENT - PANGGABEAN - NIM : 90515003, HERLINA
CO2 gas is often used as an example in the school environment because they can be obtained from simple chemical reaction which is the reaction of lime and acid. Gas synthesis apparatus made from glass material was used to synthesize CO2 gas and obtain the gas volume accurately. However, the number of equipment in school laboratory is limited, so the laboratory experiment cannot be done effectively. Glassware is risky to break and can injure the students. Therefore, small scale gas synthesis equipment which made of plastic materials is safer to be used by the students. The equipment is very practical to use, composed of easily accessible tools, and has low price. Small-scale gas synthesis equipment is assembled from large syringes as gas container, small syringes, plastic bottles, and rubber seat. The equipment can be used to measure the volume of CO2 gas and determine the purity of the sample. Small-scale gas synthesis equipment was successfully used for the synthesis of 0,04 g - 0,10 g of CaCO3 sample yielding 10,0 mL - 24,0 mL of CO2 gas. It was made by a mixture of CaCO3 solids with a ratio of 1:1 solid mass to obtain an optimal CO2 gas volume with small CaCO3 mass. It can be obtained 12,1 mL of CO2 gas from 0,1 g CaCO3 and NaCl mixture. CaCO3 solids mixture is made by other variations of the CaCO3 and KI solids reacted with H2O2 and HCl solutions. We obtained two types of gas: O2 and CO2 gas, which present in the gas reservoir, but there were no reaction between them. Other sample variations are made from a mixture of CaCO3 and NaNO2 which producing CO2 and NO gas. Both gases can react and produce NO2 gas. Small-scale gas synthesis equipment can be used for the synthesis of CO2 and other gases such as O2 and NO, and also for synthetic gases from CaCO3 solid mixture which can produce CO2 gas in both pure and mixed conditions.